Pengaruh Kepemimpinan Islami Dan Kompensasi Terhadap Kinerja Karyawan Di Bank Syariah Indonesia Kantor Cabang Bojonegoro - Sofiana, Nana; Indrarini, Rachma (Jurnal Ekonomika dan Bisnis Islam, 2022)
Bank Syariah Indonesia as an institution that operates based on public trust must have good performance. Sharia-based companies have an obligation to implement Islamic leadership and provide compensation for the performance provided by an employee in the form of compensation. The purpose of this study is to analyze the effect of Islamic leadership and compensation on employee performance partially and simultaneously at Bank Syariah Indonesia Bojonegoro Branch Office. The type of research used is field research with quantitative methods and data collection techniques through questionnaires and data processing using multiple linear regression tests on SPSS 25.0. The results of this study found the regression model Y = 3.783 + 0.620(1) + 0.303(?2) + 0.05(e) and concluded that partially or simultaneously Islamic leadership and compensation had a positive and significant effect of 72.5%